Adaptability of Yuanjiang River Valley Danaus genutia to Different Host Plants in Yunan - Jun Yao; Ting Du; Yangyang Li; Chengli Zhou; Lei Shi (Insects)
This study aims to determine the local host plant range for Yuanjiang River Valley Danaus genutia (Cramer, 1779) and evaluate the effects of different host plants on its growth, development, and reproductive success. This research assesses adult oviposition preferences and larval feeding tendencies on various host plants. An age-stage, two-sex life table was constructed to analyze the butterfly’s growth, development, reproductive success, survival rates, and other physiological aspects on different host plants. Population dynamics over the next 60 days were simulated to offer a comprehensive evaluation of the host plant suitability for D. genutia. The results indicated that D. genutia adults preferred laying eggs on Cynanchum corymbosum, followed by C. annularium, C. rostellatum, and Asclepias curassavica, with very few eggs laid on Calotropis gigantea and Dregea volubilis. Larval feeding preferences were observed in the order of C. annularium > C. corymbosum > C. rostellatum, with A. curassavica consumed only by first-instar larvae, while C. gigantea and D. volubilis were avoided. Under identical room temperature conditions, larvae feeding on C. annularium and C. corymbosum completed a full generation. Larvae feeding on C. annularium exhibited shorter developmental periods and higher early survival rates compared to those feeding on C. corymbosum, with no significant differences in adult longevity, sex ratio, or number of eggs per female. Female adults did not die immediately after laying eggs. No significant differences in the intrinsic rate of increase (r), finite rate of increase (λ), net reproduction rate (R0), or doubling time (Td) were found between populations feeding on the two host plants. However, the gross reproductive rate (GRR) and mean generation time (T) were significantly lower in the population feeding on C. corymbosum. These results confirm C. annularium and C. corymbosum as host plants for D. genutia larvae and provide a theoretical and scientific basis for the conservation of the Yuanjiang River Valley D. genutia population.